Find the solution to the system below.

Multiplying first equation with 3 and adding with second equation, we get

6x - 3y = 9

4x + 3y = 21----------------10x = 30

x = 3

Now to find y put x in any equation , say 1, so

2x - y = 3

2(3) - y = 3

6 - y = 3

6 - 3 = y

y = 3

Hence Solution is (3, 3)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up